Overcoming anemia in prospective brides and grooms as an effort to prevent stunting - Palimbo, Adriana; Bamegawati, Ika Melinda; Mahdiyah, Dede; Herawati, Anita; Rahman, Luthfia Hidayati; Fariana, Yuni Riska Nur; Arfiah (Ananda - Health & Education Foundation, 2024)
Background: Before the wedding, the majority of brides to be, still lack knowledge about reproductive health in families. After marriage, pregnancies are often not planned properly. This can have negative impacts such as the risk of pregnancy complications, disability, and even death of the mother and baby. Case presentation: In Banjarmasin, the number of prospective brides and grooms who suffer from anaemia is 7.9% and malnutrition is 11.2. Increasing a person's knowledge and attitudes regarding anaemia prevention by providing behavior and compliance in consuming iron supplement tablets or blood supplement tablets can reduce the risk of pregnancy complications and prevent stunting. Community handling was carried out together through the Midwifery Project implemented in January 2024 at the Pekauman Community Health Center. The instrument used leaflets, banners, and control cards to monitor the consumption of blood supplement tablets. Discussion: Information and educational counseling and demonstrations were used as a learning model for seven pairs of prospective brides or grooms or a total of 14 subjects. This tool uses leaflets, banners, and control cards to monitor the consumption of blood supplement tablets. Conclusion: This project has been proven to increase the bride and groom's knowledge about anaemia, its prevention and treatment, and increased compliance with taking blood supplement tablets regularly as recommended by health services.